2019
DOI: 10.1002/cbdv.201900267
|View full text |Cite
|
Sign up to set email alerts
|

Headspace Solid Phase Microextraction Coupled to GC/MS for the Analysis of Volatiles of Honeys from Arid and Mediterranean Areas of Algeria

Abstract: The volatile composition of seven honey samples collected from various regions of Algeria and feeding on different plants have been determined. The Headspace Solid‐Phase MicroExtraction (HS‐SPME) coupled with Gas Chromatography‐Mass Spectrometry (GC/MS) was used to achieve the purpose. In this work, different parameters of the HS‐SPME analytical method were investigated in order to reach maximal sensitivity, and thus to obtain maximum information about the volatile profile of Algerian honey. These parameters i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Some authors studied the characteristics of honey produced in Algeria and found differing results as to the pollen content [ 8 , 9 , 10 , 13 ], physicochemical attributes and pollen profile of samples from different areas [ 7 , 14 , 15 , 16 ], their botanical origin [ 9 , 11 , 17 , 18 , 19 ], antibacterial and antioxidant activity [ 20 ], or specific compounds such as sugars and phenolic or volatile compounds [ 21 , 22 ]. However, honey production in Algeria remains poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors studied the characteristics of honey produced in Algeria and found differing results as to the pollen content [ 8 , 9 , 10 , 13 ], physicochemical attributes and pollen profile of samples from different areas [ 7 , 14 , 15 , 16 ], their botanical origin [ 9 , 11 , 17 , 18 , 19 ], antibacterial and antioxidant activity [ 20 ], or specific compounds such as sugars and phenolic or volatile compounds [ 21 , 22 ]. However, honey production in Algeria remains poorly studied.…”
Section: Introductionmentioning
confidence: 99%
“… 64 Other multi-coating fibers used in volatomic studies are PDMS/DVB and PDMS/CAR. Costa et al 65 distinguished honeys derived from different botanical and entomological origins, while Neggad et al 66 geographically differentiated Algerian honeys from Arid and Mediterranean Areas. Headspace analysis can be conducted in either a static or a dynamic way.…”
Section: Analytical Techniques and Applicationsmentioning
confidence: 99%
“…Article Related Abbreviation: BR, biodegradable resin monosaccharides (glucose and fructose) and disaccharides (composed of both fructose and glucose linked together). Honey also contains proteins, amino acids, vitamins, minerals, organic acids, alcohols, enzymes, lipids [2], volatiles [3,4], and other substances with a wide range of biological effects, such as antioxidants, and antibacterial and other therapeutic effects [5].…”
Section: Introductionmentioning
confidence: 99%